Pyrazine and Furan Derivative Activity Prediction on Type 2 Diabetic Mellitus: In silico Study - Richa Mardianingrum; Ai Teni Siti Robi`ah; Susanti Susanti; Ruswanto Ruswanto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Diabetes Mellitus (DM) is a chronic disease that occurs when the pancreas does not produce enough insulin, or the body cannot use insulin effectively. Type 2 DM treatment can be done using antidiabetic drugs, but the continuous use of synthetic drugs will cause side effects. Empirically, the people of Nias Indonesia use palm juice (Arenga pinnata Merr.) as an antidiabetic, which can reduce blood glucose levels. This study aimed to find the active compounds in palm juice that can potentially be an antidiabetic type 2 using an in silico approach. The methods used were toxicity screening, profile pharmacokinetics, drug scanning, docking, and molecular dynamics simulation. Screening, molecular docking, and molecular dynamics of 30 compounds generated from pyrazine and furan revealed that two compounds, PF 16 and PF 30, can bind to receptors and produce lower ∆G values than metformin HCl. Molecular dynamics simulation results using the MM-GBSA calculation method showed that the PF 16 compound was more selective than the 2PDY (aldose reductase) with a value of -39.23 kcal/mol, while compound PF 30 was more selective to 1Z89 (aldose reductase) with a value of -7.36 kcal/mol. It can be concluded that the level of affinity of the PF 30 compound to the 1Z89 receptor and the PF 16 compound to the 2PDY were predicted to have the potential as antidiabetic (DM type 2).